Manipulação gênica do protozoário Neospora caninum como ferramenta para o estudo das interações parasito-hospedeiro - Mota, Caroline Martins (2016)
Neospora caninum is an obligate intracellular parasite classified in the phylum Apicomplexa, characterized by the presence of the apical complex composed by micronemes proteins, rhoptries and dense granules, used by parasite during the adhesion and invasion process of the host cell. This is the mean event in infection pathogenesis generated by N. caninum and other parasites from the phylum Apicomplexa, promoting influence in the parasite biology and the interface between the parasite and its host. Therefore, molecular tools have been developed in order to identify and characterize these possible virulence factors. Thus, the present study sought to establish a specific system of genetic manipulation of N. caninum, searching for the improvement of the genetics manipulation of this parasite. So, we developed genetically depleted N. caninum to Rop9 rhoptry using the pU6-Universal CRISPR-Cas9 plasmid of T. gondii modified by the insertion of Ku80. The Rop9 depleted parasite showed important during initial phase of invasion and replication of the parasite, however it was not characterized as a potential virulence fator for N. caninum. Furthermore, T. gondii proteins were expressed in N. caninum by the use of specific vectors for this parasite, showing an heterologous system for the study of Toxoplasma proteins, due to the fact that Gra15 or Gra24 of type II T. gondii and Rop16 of type I T. gondii were expressed in N. caninum tachyzoites in a stable way and keept its biological phenotype, as already presented the former parasite, that naturaly expresses these proteins. In addition, it was observed that N. caninum induced an inflammasome activation through NLRP3, ASC and Caspase-1. IL-1R/MyD88 demonstrated an indirect pathway in the control of parasite replication. Furthermore, it was observed that this activation is dependent of the potassium efflux and that different strains of N. caninum keep this activation profile. However, T. gondii strains block this activation, making necessary a prior signal in order to active the inflamosome pathway. Type I T. gondii Rop16 was identified as responsible for blocking this activation, in a dependent way to the STAT3 activation. Therefore, the development of molecular tools and their application in N. caninum may prove to be useful to identify and characterize virulent factors involved in the pathogenesis by these two protozoans.